2020
DOI: 10.3390/w12071890
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Evaluation of Water Quality Indices. Application into Groundwater Resources

Abstract: Until now, there was no simple procedure to test the performance of water quality indices (WQIs) or, in other words, to perform their meta-evaluation. The purpose of this study is to provide a meta-evaluation approach of two widely used WQIs and suggestions for selecting one or both of them for application in groundwater quality assessment as proposed by the European Union. The meta-evaluation concept is based on testing the performance of two widely known WQIs by applying classification of Water Frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Moreover, many regions worldwide suffer from As contamination caused by geochemical and weathering processes as well as anthropogenic activities [2,25,54,58,59]. Especially on surface and groundwater resources, more work should be done to evaluate their quality and provide a rapid method of water quality monitoring, including the Water Quality Index (WQI) approach [60]. To combat the above mentioned As related problems, water quality management incorporates efficient tools and methods for monitoring the water quality such as Water Quality Indices (WQIs) and utilizing the appropriate sources of water [16,60,61].…”
Section: Watermentioning
confidence: 99%
“…Moreover, many regions worldwide suffer from As contamination caused by geochemical and weathering processes as well as anthropogenic activities [2,25,54,58,59]. Especially on surface and groundwater resources, more work should be done to evaluate their quality and provide a rapid method of water quality monitoring, including the Water Quality Index (WQI) approach [60]. To combat the above mentioned As related problems, water quality management incorporates efficient tools and methods for monitoring the water quality such as Water Quality Indices (WQIs) and utilizing the appropriate sources of water [16,60,61].…”
Section: Watermentioning
confidence: 99%
“…The high HPI values that were attributed to Fe, Cu, and Pb resulted from mining activities [23]. Another study reported no heavy metal pollution of groundwaters in the central part of Romania, although the guideline value for Cd was slightly exceeded, due to the industrial activities developed in the nearby proximity of the groundwater sources [70]. In several other studies, HPI was also successfully used for the assessment of drinking water contamination with heavy metals [71][72][73].…”
Section: Water Quality Indicesmentioning
confidence: 99%
“…The Changjiang River flowing through the TGR is the main source of agricultural irrigation [84,85]. The acceleration of chemical weathering can cause solute changes in water, which is possible to affect the soil quality of farmland [50,81,86]. In this study, the index of SAR, Na% and RSC, which reflect the sodium hazard of irrigation water to the soil, was used to show the impact of accelerated weathering on water salinity and alkalinity.…”
Section: Potential Risks To Water Quality From Chemical Weatheringmentioning
confidence: 99%